Primary Cilia Modulate IHH Signal Transduction in Response to Hydrostatic Loading of Growth Plate Chondrocytes - Shao, Y, Yvonne Y. (2011)
Indian Hedgehog (Ihh) is a key component of the regulatory apparatus governing chondrocyte proliferation and differentiation in the growth plate. Recent studies have demonstrated that the primary cilium is the site of Ihh signaling within the cell, and that primary cilia are essential for bone and cartilage formation. Primary cilia are also postulated to act as mechanosensory organelles that transduce mechanical forces acting on the cell into biological signals. In this study, we used a hydrostatic compression system to examine Ihh signal transduction under the influence of mechanical load. Our results demonstrate that hydrostatic compression increased both Ihh gene expression and Ihh-responsive Gli-luciferase activity. These increases were aborted by disrupting the primary cilia structure with chloral hydrate. These results suggest that growth plate chondrocytes respond to hydrostatic loading by increasing Ihh signaling, and that the primary cilium is required for this mechano-biological signal transduction to occur.